2008
DOI: 10.1680/warm.2008.161.4.167
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the anaerobic biodegradation potential of MSW

Abstract: A series of laboratory tests was performed to characterise the anaerobic biodegradation potential of a fresh well-characterised sample of municipal solid waste (MSW). This characterisation included measurement of the quality and quantity of biogas produced, determination of the loss of cellulose and hemicellulose (as indicated by measurements of neutral detergent fibre (NDF) and acid detergent fibre (ADF)) and assessment of various leachate chemical characteristics at key phases during the biodegradation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…From Figure 4, it is found that the growth and dissipation time of pore gas pressure in the field tests are greater than those in the laboratory tests. Under the same gas permeability coefficient, the dissipation times of pore gas pressure calculated by field test fitting parameters were between 50 and 150 years, but those obtained by the laboratory test fitting parameters were only about 1.5 years, which are similar to the results of Ivanova et al (2008) and Liu et al (2011). Moreover, the peak values of pore gas pressure calculated by the fitting degradation parameters from field tests were much lower than those from laboratory tests.…”
Section: Gas Generation Equation and Parameter Fittingsupporting
confidence: 62%
See 1 more Smart Citation
“…From Figure 4, it is found that the growth and dissipation time of pore gas pressure in the field tests are greater than those in the laboratory tests. Under the same gas permeability coefficient, the dissipation times of pore gas pressure calculated by field test fitting parameters were between 50 and 150 years, but those obtained by the laboratory test fitting parameters were only about 1.5 years, which are similar to the results of Ivanova et al (2008) and Liu et al (2011). Moreover, the peak values of pore gas pressure calculated by the fitting degradation parameters from field tests were much lower than those from laboratory tests.…”
Section: Gas Generation Equation and Parameter Fittingsupporting
confidence: 62%
“…The durations of the five field tests were different. Ivanova et al (2008), Gioannis et al (2009), and Mahar et al (2016) provided related parameters of gas generation from laboratory tests. According to the above field and laboratory data, Equation (26) was used to fit the variation of gas generation.…”
Section: Gas Generation Equation and Parameter Fittingmentioning
confidence: 99%
“…The gas composition in both waste samples was similar with the methane content in the range of 58% -62% and the carbon dioxide content 35 -40%. The cumulative gas volume for raw MSW (collected from White's Pit waste processing plant in Southern England) degraded anaerobically for 919 days as reported in [28] was significantly higher (243.55 L kg -1 DM) which is attributable to the higher organic waste composition in the raw MSW. This reduced gassing potential of the MBT wastes demonstrates diversion of the degradable fraction from disposal to landfill as a result of the biological pre-treatment process, but also that landfill gas control measures will still be required to prevent fugitive gas emissions from landfill.…”
Section: Biogas Volume and Compositionmentioning
confidence: 83%
“…TC and TN contents of the samples were measured using a CE Instruments Flash EA 1112 Elemental Analyser (Thermo Finnigan). Fibre analysis using the FibreCap test method was performed for the measurement of cellulose, hemicellulose and lignin content as described in [27] and [28].…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…From these, 45 studies were considered sufficiently comprehensive and were selected for further analysis. A database consisting of 49 laboratory experiments (Eleazer et al 1997;Borglin et al 2004;He et al 2005;Francois et al 2006;Dearman and Bentham 2007;Faour et al 2007;Zheng et al 2007;Erses et al 2008;Ivanova et al 2008a;Ivanova et al 2008b;Qu et al 2009;Valencia et al 2009;Gourc et al 2010;Abbassi-Guendouz et al 2012;Cho et al 2012;Huang et al 2012;Mali et al 2012;Bareither et al 2013b;Staub et al 2013;Fei et al 2014aFei et al , 2015 and field monitoring data from 57 landfills was compiled (El-Fadel et al 1996;Morris et al 2003;Bentley et al 2005;Budka et al 2007;Faour et al 2007;Willumsen 2007;Machado et al 2009;Thompson et al 2009;Barlaz et al 2010a;Tolaymat et al 2010;Amini et al 2012;Lamborn 2012;Yazdani et al 2012;Amini et al 2013;Oonk et al 2013;Sormunen et al 2013;Wang et al 2013;Zhao et al 2013). The source and composition of waste, and operating and environmental conditions for / 30 bi...…”
Section: Literature Review and Classification Of Biodegradation Condimentioning
confidence: 99%